👤

Rownania
1) 4/9 x - 2 = 5/12 x - 1 i 1/3
2) (x-5)/8 - 5x/12 = 1,5
3) 3 [ 3 (3x-4) -4 ] -7 = -2 [ -2 (-2x+5) +5 ] +5


Odpowiedź :

Odpowiedź:

1) 4/9x-5/12x=2-1 i 1/3 / sprowadzamy do wspolnego mianownika :

16/36x-15/36x=2/3

1/36x=2/3 / :1/36

x=2/3 *36/1

x=24

2)  

(x-5)8-5x/12=1,5

8x-40-5x/12=1,5   /*12

96x-480-5x=18

96x-5x=18+480

91x=498 /:91

x=5 i 43/91

3)

3{3(3x-4)-4}-7=-2{-2(-2x+5)+5}+5

3(9x-12-4)-7=-2(4x-10+5)+5

27x-36-12=-8x+20-10+5

27x-48=8x+15

27x-8x=15+48

19x=63 /:19

x=3 i 6/63

x=3i2/21

Szczegółowe wyjaśnienie: